PENINGKATAN KEMAMPUAN MEMAHAMI KAIDAH TAJWID DAN MAKHARIJ AL-HURUF MATA PELAJARAN PAI MATERI QS. YUNUS [10]: 40-41 DAN QS. AL-MAIDAH [5]: 32 MELALUI APLIKASI TAJWID Qt-MEDIA PADA SISWA KELAS XI SMA NEGERI 1 SANGKULIRANG - Surono Surono (STAI Sangatta Kutai Timur, 2021)
This study aims to determine the use of the Qt-Media application in improving the ability to understand the rule of tajweed and makharij al-huruf in PAI subjects in QS. Yunus [10]: 40-41 and QS. al-Maidah [5]: 32. The results of the action in this study indicate that the treatment of learning in Cycle I by using the Qt-Media application as the learning implementation plan, then the ability of students to understand the tajweed and makharij al-huruf in QS. Yunus [10]: 40-41 and QS. al-Maidah [5]: 32 through the Qt-Media application, the average value is 79.17, with a completeness rate of 79%. Meanwhile, in the second cycle, with the improvement of learning and the learning implementation plan due to the reflection of Cycle I, the average ability of students to understand the rules of tajweed and makharij al-huruf in QS. Yunus [10]: 40-41 and QS. al-Maidah [5]: 32 through the Qt-Media application, the average value is 95.83, with a completeness rate of 95.83%.